Severe early‐onset manifestations of pseudoxanthoma elasticum resulting from the cumulative effects of several deleterious mutations in ENPP1, ABCC6 and HBB: transient improvement in ectopic calcification with sodium thiosulfate. (1st August 2020) - Omarjee, L.; Nitschke, Y.; Verschuere, S.; Bourrat, E.; Vignon, M.‐D.; Navasiolava, N.; Leftheriotis, G.; Kauffenstein, G.; Rutsch, F.; Vanakker, O.M.; Martin, L.
Summary: Pseudoxanthoma elasticum (PXE) is a rare disorder characterized by fragmentation and progressive calcification of elastic fibres in connective tissues. Overlap has been reported between the inherited PXE phenotype associated with ENPP1, ABCC6 or NT5E mutations and acquired PXE clinical manifestations associated with haemoglobinopathies induced by HBB mutations. No treatment is currently available for PXE. A young boy presented with severe early‐onset systemic calcifications occurring in the skin as elastosis perforans serpiginosa (EPS) and in the arteries, causing mesenteric and limb ischaemia. Analyses revealed deleterious ABCC6, ENPP1 and HBB mutations. The diagnosis of severe PXE was retained and we have coined the term 'PXE+ syndrome' to describe the cumulative effects of the various mutations in this uncommon phenotype. Given the severity, rapid progression and a potentially fatal prognosis, intravenous sodium thiosulfate (STS) was initiated at 25 g three times weekly for 6 months. Numerous side‐effects prompted dosage adjustment to 10 g intravenously daily. Treatment efficacy was evaluated at 6 months. Asthaenia, anorexia and pre‐/postprandial pain had subsided, entailing weight gain. Abdominal EPS had diminished. Calcific stenosis of the coeliac and mesenteric arteries was no longer detectable on arterial ultrasonography. Follow‐up revealed only transient efficacy of STS. Discontinuation of treatment to evaluate the persistence of effects resulted in relapse of the initial symptomatology after 4 months. STS efficacy is conceivably due to strong antioxidant properties and chelation of calcium to form soluble calcium thiosulfate complexes. This case is suggestive of PXE+ syndrome for which STS may represent potential treatment in severe cases. What's already known about this topic? Generalized arterial calcification of infancy may occur in association with ABCC6 mutations and pseudoxanthoma elasticum (PXE) can be linked to ENPP1 mutations. A PXE‐like phenotype has also been reported in a subset of patients with inherited haemoglobinopathies, namely sickle cell disease or β‐thalassaemia, related to HBB mutations. To date, there is still no cure for PXE. What does this study add? We report a severe case of PXE resulting from the cumulative effects of several deleterious mutations in ENPP1, ABCC6 and HBB . We suggest the term 'PXE+ syndrome' to describe such patients. Sodium thiosulfate therapy could represent a potential option in severe cases of PXE+ syndrome.